Productive performance appraisals - Falcone, Paul (WorkSmart series., 2007)
"Productive Performance Appraisals is a fast and easy guide for turning the dreaded performance appraisal into a constructive, collaborative effort. The book gives you all the easy-to-use tools you need to conduct an effective review - including sample dialogs, checklists, and forms." "In addition, this completely updated edition contains new sections on rating employees, justifying scores, and weaving disciplinary language into the review. The book gives you guidance on developing career plans, keeping consistent records, communicating changes in roles, how reviews are used when determining layoffs, and much more."--Jacket.